Design and development of an android-based cultural heritage application: A case study of fakfak, west Papua - Arridha, Riyadh; Anas, Syukron; Roy, Andi; Armando, Putra; Ismun, Ismun (Jurnal Mandiri IT, 2025)
This study aims to design and develop an Android-based cultural heritage application to introduce and preserve cultural sites in Fakfak Regency, West Papua. The application provides information on cultural heritage sites, map locations, and navigation routes to these sites. The development process followed the Waterfall model, encompassing requirements analysis, design, coding, testing, and maintenance stages. Application testing was conducted using the Black Box method to evaluate system functionality and usability testing with a Likert scale to measure user satisfaction. The test results indicate that the application is easily accessible, provides accurate information, and features a user-friendly interface, achieving an average user satisfaction rate of 90%. This application is expected to serve as an effective tool for preserving and promoting cultural heritage in Fakfak Regency.